Aspek Yuridis Pengelolaan Keuangan Negara Pada Kementerian/Lembaga Dihubungkan Dengan Prinsip Good Governance Berdasarkan Undang-undang No. 17 Tahun 2003 Tentang Keuangan Negara - Widiawaty Widiawaty (Jurnal Media Justitia Nusantara, 2016)
Law Of The Republic Indonesia Number 17 Years 2003 concerting Public Money said that the public money must to managed in an orderly, obedient to the laws and regulations, efficient, economical, effective, transparent, and accountable with regard sense of justice and propriety. This mandate was in line with the government's efforts in order to realize good governance in the management of public money, which in turn can achieve welfare and prosperity of the people. The reality saw that there were some problems in public money managements, public money was not cordance with the principles of good governance. The research analyzed used Welfarestate theory as grand theory, Hans Kelsen’s theory as middle theory, and Hukum Pembangunan Moehtar’s theory as applied theory. This research was used normative juridical methodology, this mean thatreviewed legislation and legal theories related to the subject matter covered. This research was used secondary data such as literatures and interviews. Analysis of the data used was qualitative juridical. The result of this research saw that public money’s management was not did by good governanceprinciples approriately yet. In future, principle of good governance must did firmly. Improvements of laws and regulations about management of public money must be done in order to make a good governance’s not only about value, but also, in the end can help achieve national goals to create social welfare state.